THE EFFORTS TO INCREASE TEXT RECOUNT WRITING BY USING FLOW SENTENCE TECHNIQUES SEMESTER III OF ABA BALIKPAPAN - Muhammad Rochman (UIBU, 2020)
The background of this research is based on the fact that learning outcomes of the the written recount text is still not as expected. Therefore there needs to be an effort from the lecturer to improve the learning outcomes. This research generally aims to improve students' recount text writing skills. Specifically, this research aims for: 1) Obtaining information about whether or not the flow sentence technique can improve recount text writing skills, 2) Obtain information about the ability of sentence techniques flow increases student participation in learning to write recount texts. Procedure This Classroom Action Research includes stages: (1) action planning (2) implementation actions, (3) observation and interpretation, and (4) analysis and reflection. This research was designed in two cycles using flow sentence techniques. The research instrument uses test and observation techniques. Data analysis techniques use Descriptive analysis, i.e. student learning outcomes were analyzed by describing inter-test scores cycle with performance indicators. Observation results were analyzed descriptively based on results observation and reflection. The results of this Classroom Action Research are: initial conditions 15 students or 46% are incomplete, 17 students or 54% complete. In cycle I 8 students or 25% are incomplete, 24 students or 75% complete. In Cycle II 4 students or 12.5% ​​did not complete, 28 students or 87.5% complete. The results of the study concluded that the use of the technique flowing sentences can improve students' recount text writing skills third semester academic year 2019/2020 of ABA Balikpapan. Flowing sentence techniques can also increase student participation in learning to write recount texts. With a classical completeness level of 87.5% in the second cycle show that the learning improvement effort has been successful. The sentence technique is effective used to improve recount text writing skills.